Clinical Significance of Hilar Hyalinosis in Glomeruli of Children with Idiopathic Nephrotic Syndrome - Amal AAl-Eisa; Thomas M D'souza (Archives of Renal Diseases and Management - Peertechz Publications, 2015)
Introduction: Hilar hyalinosis (HH) of glomeruli has been thought for a long time to be a precursor or a variant of focal glomerulosclerosis (FGS). In view of its implications on treatment and prognosis of nephrotic syndrome, a retrospective study of hilar hyalinosis in children with the idiopathic nephrotic syndrome (INS), but without any other histologic evidence of FGS, was performed to determine the clinic-pathologic significance of this lesion. Methods: A total of 92 Children with INS who had kidney biopsies for frequent relapses, steroid dependency  or  resistance  were  included.  Eight  of  them  had  a  biopsy-proven  diagnosis  of  either minimal change disease or mild IgM nephropathy with HH in 6-25% of glomeruli were compared to control group consisting of 84 children with either minimal change disease (n=57) or IgM nephropathy (n=27) but without HH. Results: Clinically  HH  patients  presented  with  NS  and  followed  a  steroid-dependent  relapsing course prior to biopsy. Around 75% of the HH patients received at least one course of cytotoxic therapy after biopsy. At last visit, 6 patients were in remission, 2 were protein-free but on medication. None had hypertension or renal insufficiency. Apart from having a shorter interval between presentation and biopsy (P<0.001) and a lower remission rate (P<0.05), control patients followed a similar course.Pathologically  HH  patients  showed  less  mesangial  change  (P<0.001)  than  the  controls  but  similar mean glomerular size and tubuloinerstitial damage.